Assessing the impact of recent global crisis on Small and Medium Enterprises (SMES): evidence from Indonesia / Tri Winarno. - Winarno, Tri (Universiti Teknologi Mara Selangor, 2013)
In this article we examine three broad issues. The first is to measure the impact of 2008 global financial crisis on Indonesia’s economy, particularly on loans extended to small and medium scale enterprises at regional level. Next is to analyze significant factors of inducing loans extended to small and medium scale enterprises. Finally, it is to fill the gap in the literature by introducing a quantitative methodology. A spatial lag model and spatial error model are used to assess the three broad issues. Regionally, quarterly panel data spanning from 2002 up to 2011 are employed to support the analysis. One of the results is the global financial crisis that negatively impacts on Indonesia economy, particularly on the performance of small and medium enterprises (SMEs). In terms of loan extended to the SMEs, there is strong and positive spatially correlation among province, showing commoving and integrating economy within the territories of Indonesia. Finally, this research suggests that interest rates is not significantly correlated with loans to SMEs, which indicates that the access to financial institutions is more important and urgent to boost the performance of SMEs in Indonesia which is reinforcing the opinion of financial inclusions for SMEs.